INTERACTIVE RADIO: GREEN TRANSFORMATION – TOWARDS SUSTAINABLE ECONOMY IN INDONESIA - Ilyona Risty; Hananiel M Gunawan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
The implementation of Community Service (PKM) for the period of December 2024 was carried out by a Team from the Faculty of Economics and Business School UPH Surabaya Campus together with Radio Sangkakala Surabaya as partners. Therefore, Universitas Pelita Harapan Surabaya Campus collaborated with Radio Sangkakala Surabaya to be able to provide education to the wider community. This collaboration was built by presenting quality speakers from the Management Study Program and the Accounting Study Program. Each speaker will present interesting topics that are in accordance with current issues. Based on discussions regarding community needs, this PKM was carried out by providing supplies to the Community with the theme of Green Economy. With the holding of this interactive talk show, it is hoped that it can provide information and educational education for the wider community in the Surabaya area in terms of economics, business and sustainability issues that can improve community knowledge and skills.